Cultural essentialism and tailored hotel service for Chinese: the moderating role of satisfaction. Issue 9 (9th September 2019) - Fong, Lawrence Hoc Nang; He, Hongwei; Chao, Melody Manchi; Leandro, Galli; King, David
Abstract : Purpose: The purpose of this study is to understand Chinese consumers' responses to ethnically tailored hotel services from the theoretical perspective of cultural essentialism. Design/methodology/approach: Data collection was conducted through an online survey with Chinese respondents. Hierarchical moderated regression was performed to analyze the data. Findings: The results show a positive relationship between cultural essentialism and consumer responses to hotel services that are tailored to their culture. Furthermore, the findings show that prior service satisfaction does not only positively influence the consumer responses, but also amplifies the link between cultural essentialism and the consumer responses. Practical implications: Hoteliers are recommended to consider the cultural essentialism of Chinese consumers when adaptive services are introduced. Hotel services that are tailored to Chinese culture is a viable strategy if most Chinese customers are cultural essentialists. Originality/value: This study adds knowledge to the hospitality scholarship by introducing cultural essentialism and demonstrating its role in influencing consumer preferences for familiarity as opposed to exotic hotel services. Furthermore, the moderating role of service satisfaction extends the consumer behavior literature.